Transcriptomic Responses of Salmonella enterica Serovars Enteritidis in Sodium Hypochlorite - Wang, Sheng; Xiao, Xingning; Qiu, Mengjia; Wang, Wensi; Xiao, Yingping; Yang, Hua; Dang, Yali; Wang, Wen (Frontiers in Cellular and Infection Microbiology, 2022)
Salmonella enterica serovars Enteritidis (S. Enteritidis) can survive extreme food processing environments including bactericidal sodium hypochlorite (NaClO) treatments generally recognized as safe. In order to reveal the molecular regulatory mechanisms underlying the phenotypes, the overall regulation of genes at the transcription level in S. Enteritidis after NaClO stimulation were investigated by RNA-sequencing. We identified 1399 differentially expressed genes (DEG) of S. Enteritidis strain CVCC 1806 following treatment in liquid culture with 100 mg/L NaClO for 20 min (915 upregulated and 484 downregulated). NaClO stress affects the transcription of genes related to a range of important biomolecular processes such as membrane damage, membrane transport function, energy metabolism, oxidative stress, DNA repair, and other important processes in Salmonella enterica. First, NaClO affects the structural stability of cell membranes, which induces the expression of a range of outer and inner membrane proteins. This may lead to changes in cell membrane permeability, accelerating the frequency of DNA conversion and contributing to the production of drug-resistant bacteria. In addition, the expression of exocytosis pump genes (emrB, yceE, ydhE, and ydhC) was able to expel NaClO from the cell, thereby increasing bacterial tolerance to NaClO. Secondly, downregulation of genes related to the Kdp-ATPase transporter system (kdpABC) and the amino acid transporter system (aroP, brnQ and livF) may to some extent reduce active transport by bacterial cells, thereby reducing their own metabolism and the entry of disinfectants. Downregulation of genes related to the tricarboxylic acid (TCA) cycle may drive bacterial cells into a viable but non-culturable (VBNC) state, resisting NaClO attack by reducing energy metabolism. In addition, significant upregulation of genes related to oxidative stress could mitigate damage caused by disinfectants by eliminating alkyl hydroperoxides, while upregulation of genes related to DNA repair could repair damage to bacterial cells caused by oxidative stress. Therefore, this study indicated that S. Enteritidis has genomic mechanisms to adapt to NaClO stress.